Exogenous melatonin alleviates premature ovarian failure by regulating granulosa cell autophagy - Guang-hu Zhou; Ye-fei He; Hai-ling Wang; Yi-bo Lv; Yi-mei Cong; Zhen-long Sun; Xiao-wen Jiang; Wen-hui Yu (npj Regenerative Medicine)
Abstract Premature ovarian failure (POF) is a disease closely related to the apoptosis of granulosa cells (GCs) in the follicle. In this study, exogenous melatonin (Mel) was used to interfere with POF model mice, so as to provide reference for Mel prevention and treatment of POF. Mel could promote estrogen secretion and improve ovarian physiological function in mice. In GCs, mitochondrial membrane potential increases and ATP content increases, LC3/LC3-LL and Beclin1 expression increases, p62 expression decreases, which promoted the occurrence of autophagy. Intersecting target screening, GO and KEGG enrichment analysis of Mel and POF revealed that estrogen receptor 1 (ESR1) was the most compatible target for Mel action; meanwhile, Mel had a high enrichment value in the PI3K-AKT-mTOR pathway. It was detected that Mel could increase the expression of ESR1 and inhibit the phosphorylation levels of PI3K, AKT, and mTOR to promote autophagy and reduce apoptosis of GCs.